Are we getting any better at staying better? The long view on relapse and recovery in first episode nonaffective psychosis and schizophrenia. (September 2019) - Taylor, Mark; Jauhar, Sameer
Relapse in, and recovery from, schizophrenia has been acknowledged since the disease was first described. In this review the authors summarize the long-term (>100 years) data on relapse and recovery in schizophrenia by reviewing the extant older and modern relevant literature. The authors systematically question the utility of pharmacological and nonpharmacological interventions, with an emphasis on first episode nonaffective psychosis. The method used is a narrative review of earlier meta-analytic and systematic reviews. Antipsychotic medication discontinuation studies suggest a role for prophylactic maintenance treatment in the majority of people with schizophrenia, despite recent debate on this subject. The authors conclude that long-term outcomes, including relapse and recovery rates, have improved in the last 100 years, though prospectively identifying those people who do not require long-term antipsychotic treatment has not yet been possible. Data also suggests that interventions and outcomes during the first 5 years of the disease can influence the long-term schizophrenia trajectory.